Description of Absorption Distribution Metabolism Excretion Toxicity (ADMET) of Nuciferine from Terate Flowers (Nymphaea spp.) using pkCSM Technology - Prasetyawan, Fendy; Saristiana, Yuneka; Kadir, Mujtahid Bin And; Savitri, Lisa; Salmasfattah, Novyananda; Fadel, Muhammad Nurul; Besan, Emma Jayanti (Journal of Engineering Science and Technology Management (JES-TM), 2025)
This study evaluates the ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) profile of nuciferine to assess its potential as a drug candidate. Based on in silico analysis, nuciferine demonstrates favorable oral absorption and extensive systemic distribution, including its capability to cross the blood-brain barrier into the central nervous system. Regarding metabolism, the compound acts as a substrate for CYP2D6 and CYP3A4 enzymes while serving as an inhibitor of CYP1A2 and CYP2D6, which may lead to drug-drug interactions. In terms of excretion, nuciferine displays moderate clearance values and utilizes renal transporter OCT2. However, toxicological evaluations suggest potential risks, including mutagenicity (positive AMES test), hepatotoxicity, and inhibition of hERG II potassium channels, which are associated with cardiotoxicity risks. Despite its favorable bioavailability and distribution properties, concerns about chronic toxic effects and metabolic interaction risks underscore the need for careful consideration in its development. Further research is necessary to validate its safety and efficacy for therapeutic applications.